Prevalencia de tabaquismo y grado de adicción a la nicotina en adolescentes - Luque Herrera, Leopoldo (Universidad Michoacana de San Nicolás de Hidalgo, 2007)
Prevalence of smoking and degree of nicotine addiction in adolescents. Introduction: Tobacco use is a global public health problem. According to the World Health Organization, smoking is the second leading preventable death camp in the world, with nearly 5 million deaths annually. Information and analysis on tobacco consumption are essential to be successful in combating the disease and thus provide adequate guidance on prevention and control measures. Smoking is a chronic, addictive disease, the age of onset predominates in adolescence, damage and treatment are related to the degree of addiction to nicotine. Objectives: To know the prevalence of smoking and degree of nicotine addiction in adolescents. Material and methods: A cross-sectional, retrospective, descriptive, cross-sectional study was conducted in 314 adolescents between 14 and 19 years of age at Melchor Ocampo High School, U.M.S.N.H. Sample size procedure was used for the finite population, with sampling for convenience. The survey consists of two parts the first to know the prevalence of smoking and the second assesses the degree of addiction to nicotine. Results: The overall prevalence of smoking was 33%. The degree of addiction to nicotine was 90% mild, 9% moderate, 1% severe. The prevalence of smoking in men was 34% and women 32%. The degree of nicotine addiction in men was 90% mild, 8% moderate, 2% severe and in women 91% mild, 9% moderate, none to severe degree. 59% of teenagers ever smoked cigarettes, and 41% never smoked. They started smoking cigarettes at 7 years or younger, 7% of adolescents, 8 to 9 years old 3%, 10 to 11 years old 4%, 12 to 13 years old 14%, 14 to 15 years old 23%, 16 more years 12% .

El consumo de tabaco es un problema de salud pública mundial. De acuerdo con la Organización Mundial de la Salud, el tabaquismo es la segunda casa principal de muerte prevenible en el mundo, con casi 5 millones de defunciones anuales. La información y análisis sobre el consumo de tabaco son indispensables para tener éxito en la lucha contra la enfermedad y así orientar de manera adecuada las medidas de prevención y control. El tabaquismo es una enfermedad crónica, adictiva, la edad de inicio predomina en la adolescencia, el daño y tratamiento esta relacionados con el grado de adicción a la nicotina. Objetivos: Conocer la prevalencia de tabaquismo y grado de adicción a la nicotina en adolescentes. Material y métodos: Se realizó estudio, observacional, descriptivo, transversal y retrospectivo, tipo encuesta en 314 adolescentes entre 14 y 19 años, en la Preparatoria Melchor Ocampo de la U.M.S.N.H. Se empleó procedimiento de tamaño de la muestra para la población finita, con muestreo por conveniencia. La encuesta consta de dos partes la primera para conocer la prevalecía de tabaquismo y la segunda evalúa grado de adicción a la nicotina. Resultados: La prevalencia global de tabaquismo fue 33%. El grado de adicción a la nicotina 90% leve, 9% moderado, 1% severo. La prevalencia de tabaquismo en hombres de 34% y mujeres 32%. El grado de adicción a la nicotina en hombres 90% leve, 8% moderado, 2% severo y en las mujeres 91% leve, 9% moderado, ninguna en grado severo. El 59% de adolescentes fumaron cigarrillo alguna vez en su vida, y el 41% nunca han fumado. Iniciaron a fumar cigarrillos a los 7 años o menos el 7% de adolescentes, de 8 a 9 años 3%, 10 a 11 años 4%, 12 a 13 años 14%, 14 a 15 años 23%, 16 más años 12%.
Facultad de Ciencias Médicas y Biológicas. Especialidad en Medicina Familiar
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4104; info:eu-repo/classification/cti/3; FCMB-E-2007-0005; Tabaquismo; Adicción; Adolescentes